High shear stress relates to intraplaque haemorrhage in asymptomatic carotid plaques. (August 2016) - Tuenter, A.; Selwaness, M.; Arias Lorza, A.; Schuurbiers, J.C.H.; Speelman, L.; Cibis, M.; van der Lugt, A.; de Bruijne, M.; van der Steen, A.F.W.; Franco, O.H.; Vernooij, M.W.; Wentzel, J.J.
Abstract: Background and aims: Carotid artery plaques with vulnerable plaque components are related to a higher risk of cerebrovascular accidents. It is unknown which factors drive vulnerable plaque development. Shear stress, the frictional force of blood at the vessel wall, is known to influence plaque formation. We evaluated the association between shear stress and plaque components (intraplaque haemorrhage (IPH), lipid rich necrotic core (LRNC) and/or calcifications) in relatively small carotid artery plaques in asymptomatic persons. Methods: Participants (n = 74) from the population-based Rotterdam Study, all with carotid atherosclerosis assessed on ultrasound, underwent carotid MRI. Multiple MRI sequences were used to evaluate the presence of IPH, LRNC and/or calcifications in plaques in the carotid arteries. Images were automatically segmented for lumen and outer wall to obtain a 3D reconstruction of the carotid bifurcation. These reconstructions were used to calculate minimum, mean and maximum shear stresses by applying computational fluid dynamics with subject-specific inflow conditions. Associations between shear stress measures and plaque composition were studied using generalized estimating equations analysis, adjusting for age, sex and carotid wall thickness. Results: The study group consisted of 93 atherosclerotic carotid arteries of 74 participants. In plaques with higher maximum shear stresses, IPH was more often present (OR per unit increase in maximum shear stress (log transformed) = 12.14; p  = 0.001). Higher maximum shear stress was also significantly associated with the presence of calcifications (OR = 4.28; p  = 0.015). Conclusions: Higher maximum shear stress is associated with intraplaque haemorrhage and calcifications. Highlights: The association between shear stress and MRI-based plaque components was studied. Fusion of multi-sequence MRI and computational fluid dynamics was performed. 92 asymptomatic carotid arteries from a population based study were included. Higher shear stress is associated with intraplaque haemorrhage and calcifications.